Novel treatment from a botanical formulation Si-Miao-Yong-an decoction inhibits vasa vasorum angiogenesis and stabilizes atherosclerosis plaques via the Wnt1/β-catenin signalling pathway - Zhongwen Qi; Zhipeng Yan; Ke Zhu; Yueyao Wang; Yajie Fan; Tingting Li; Junping Zhang (Pharmaceutical Biology, 2023)
AbstractContext Si-Miao-Yong-An (SMYA) has been widely used for the clinical treatment of atherosclerosis (AS). Yet, its complete mechanism of action is not fully understood.Objective To investigate the mechanism by which SMYA stabilizes AS plaques from the perspective of inhibiting vasa vasorum (VV) angiogenesis.Materials and methods We used male ApoE-/- mice to establish an AS model. The mice were divided into model, SMYA (11.7 mg/kg/d), and simvastatin (SVTT) (2.6 mg/kg/d) groups. Mice were given SMYA or SVTT by daily gavage for 8 weeks. HE staining, immunofluorescence double-labelling staining, and immunohistochemical staining were used to observe the pathological changes in the plaques. Finally, the protein and mRNA expression levels of the Wnt1/β-catenin signalling pathway were detected by Western blot and qRT-PCR, respectively.Results SMYA significantly attenuated cholesterol crystallization, and lipid accumulation in AS plaques, resulting in smaller plaque size (0.25 mm2 vs. 0.46 mm2), and lowering ratio of plaque to lumen area (20.04% vs. 38.33%) and VV density (50.64/mm2 vs. 98.02/mm2). Meanwhile, SMYA suppressed both the positive area percentage of Wnt1 (2.53 vs. 3.56), β-catenin (3.33 vs. 5.65) and Cyclin D1 (2.10 vs. 3.27) proteins in the aortic root plaques, and mRNA expression of Wnt1 (1.38 vs. 2.09), β-catenin (2.05 vs. 3.25) and Cyclin D1 (1.39 vs. 2.57).Discussion and conclusions SMYA has a protective effect against AS, which may be related to its anti-VV angiogenesis in plaques, suggesting that SMYA has the potential as a novel botanical formulation in the treatment of AS.